Method for determining anti-pressure capability of lithium cobalt oxide material
By measuring the specific surface area of lithium cobalt oxide powder samples under different pressures, the problem that the prior art cannot accurately evaluate the compressive resistance of lithium cobalt oxide materials is solved, and efficient and low-cost detection is achieved, and lithium cobalt oxide materials are provided. Full support for performance.
Patent Information
- Application Number
- CN202310784470.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art cannot accurately and comprehensively evaluate the compressive resistance of lithium cobalt oxide materials, and the commonly used methods have limitations and high costs, and cannot effectively reflect the crushing of the material during the charge and discharge cycle.
By measuring the specific surface area of lithium cobalt oxide powder sample under different pressure factors, establishing the relationship between specific surface area and pressure factors, it evaluates its compressive resistance, and adopts multi-wheel multi-channel method and group cross-calibration method to improve detection accuracy and Efficiency, reduce costs.
A comprehensive and accurate assessment of the compressive resistance of lithium cobalt oxide materials has been achieved, the detection efficiency and cost-effectiveness have been improved, the limitations of micro-observation have been avoided, and technical support for the performance of lithium cobalt oxide materials has been provided.
Smart Images

Figure CN119223742A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of electrode positive electrode material testing, and specifically relates to a method for determining the compressive strength of a lithium cobalt oxide material. Background Art
[0002] Lithium cobalt oxide materials are subject to pressure during the cold pressing process of the pole pieces, and stress is generated during the charge and discharge cycle due to repeated lithium insertion and extraction, which can easily cause microcracks. In severe cases, they may even crack and form broken particles, affecting the electrochemical performance of lithium-ion batteries. During the service of lithium cobalt oxide materials, even small microcracks may cause the intrusion of electrolyte, resulting in the formation of a Co3O4-like impurity passivation layer inside and outside the particles, thereby increasing the charge exchange impedance, hindering the transfer of ions and electrons at the grain boundaries, and ultimately causing the lithium cobalt oxide material to be wrapped and inactivated by the passivation layer.
[0003] Therefore, in order to improve the comprehensive performance of lithium cobalt oxide materials and the electrochemical performance of lithium-ion batteries, it is necessary to accurately test the compressive capacity of lithium cobalt oxide materials. The existing technology generally uses scanning electron microscope observation of the cross section obtained by Ar ion beam cutting to judge the compressive capacity of lithium cobalt oxide materials by observing cracks or breakage. This method can only be evaluated on a local two-dimensional micro-area scale, and additional particle breakage may occur during the cutting process. It has great limitations and cannot accurately and comprehensively characterize the compressive capacity of lithium cobalt oxide materials. Summary of the invention
[0004] In order to solve the problems and shortcomings of the prior art, the present application provides a method for determining the compressive resistance of lithium cobalt oxide materials. By obtaining the specific surface area of the lithium cobalt oxide powder sample under different pressure factors, the degree of particle breakage of the lithium cobalt oxide is quantified by the specific surface area, and then the compressive resistance is evaluated. This method can comprehensively and accurately reflect the overall compressive resistance of the lithium cobalt oxide powder, and has high detection efficiency and low cost.
[0005] This application provides a method for determining the compressive strength of lithium cobalt oxide materials, and the scheme adopted is as follows:
[0006] A method for determining the compressive strength of a lithium cobalt oxide material comprises at least the following steps: step S1, obtaining a lithium cobalt oxide powder sample to be tested; step S2, obtaining a pressure factor T of the lithium cobalt oxide powder sample to be tested in step S1 and a specific surface area corresponding to the lithium cobalt oxide powder sample to be tested Step S3: based on the pressure factor T and specific surface area Determine the compressive resistance of the lithium cobalt oxide material. The present application tests the corresponding specific surface area of the lithium cobalt oxide powder sample under different pressure factors, establishes the corresponding relationship between the specific surface area and the pressure factor, and reflects the crushing of the lithium cobalt oxide powder sample under different pressure factors through the specific surface area, thereby determining the compressive resistance of the lithium cobalt oxide material. This method does not require high-precision and high-cost microscopic detection equipment, and can characterize the crushing and compressive resistance of the lithium cobalt oxide material from a macroscopic perspective. It has the advantages of accurate and comprehensive test results, and can provide technical support for breakthrough improvements in the performance of lithium cobalt oxide materials. It also has the advantages of simple method, high detection efficiency and low cost.
[0007] Preferably, step S1 includes: pressurizing the lithium cobalt oxide powder to obtain the lithium cobalt oxide powder sample to be tested; or sintering the lithium cobalt oxide positive electrode sheet to be tested to remove the binder and the conductive agent to obtain the lithium cobalt oxide powder sample to be tested. The method for determining the compressive resistance provided in the present application can be used to test the lithium cobalt oxide powder or the lithium cobalt oxide positive electrode sheet. The compressive resistance of the lithium cobalt oxide powder can be directly detected by using the lithium cobalt oxide powder as the test object. The compressive resistance of the lithium cobalt oxide powder after interacting with the binder, the conductive agent, and the current collector during the actual preparation process can be detected by using the lithium cobalt oxide positive electrode sheet as the test object.
[0008] Preferably, the conditions for the pressure treatment in step S1 include: a pressure of 0 to 8t and a pressure holding time of 3 to 20min. The lithium cobalt oxide powder sample to be tested is subjected to pressure treatment to be crushed, and then the degree of crushing of the lithium cobalt oxide powder under different pressure treatment conditions can be used to determine its compressive resistance. Among them, when the pressure is 0, the lithium cobalt oxide powder sample to be tested is treated according to the pressure treatment process without applying pressure. The test with a pressure of 0 can be used as a control group and compared with other different pressure groups.
[0009] Furthermore, in order to ensure the crushing effect of the lithium cobalt oxide powder to be tested and improve the detection efficiency, the pressure of the pressurization treatment is 5 to 8 tons, and the pressure holding time is 3 to 10 minutes.
[0010] Preferably, the conditions for the sintering treatment in step S1 include: a sintering temperature of 600-800° C. and a sintering time of 2-4 hours. Under these conditions, the conductive agent and binder of the lithium cobalt oxide positive electrode sheet can be removed, and the cracking or agglomeration of the lithium cobalt oxide can be avoided or reduced, and the influence of the sintering process on the lithium cobalt oxide powder particles can be reduced, which is conducive to accurately obtaining the specific surface area results of the lithium cobalt oxide material and improving the accuracy of the detection.
[0011] Preferably, the lithium cobalt oxide positive electrode sheets are sheared and suspended, and sintered under the condition that there are gaps between different lithium cobalt oxide positive electrode sheets. The size of the lithium cobalt oxide positive electrode sheets after shearing can be determined according to the equipment for sintering treatment. The suspension treatment can be performed by punching holes at the top of the lithium cobalt oxide positive electrode sheets, hanging the positive electrode sheets on the bracket through the holes, or clamping the top of the sheets with a clip. Through shearing and suspension treatment, gaps are created between different lithium cobalt oxide positive electrode sheets, reducing the contact of the sheets during sintering, which is beneficial to heat dissipation and uniform heating of the sheets, thereby reducing the local temperature caused by poor heat dissipation at the contact position of the sheets, and minimizing the melting of aluminum foil or the reaction with lithium cobalt oxide, which leads to a larger specific surface area test result, thereby ensuring the accuracy of subsequent specific surface area measurement. In addition, the sintering treatment method of the present application can make full use of the space in the sintering furnace, which is beneficial to simultaneously process more sheets and ensure excellent sintering treatment effects, so that more lithium cobalt oxide powder samples to be tested can be obtained, and the detection efficiency of compressive resistance can be improved.
[0012] Preferably, the pressure factor in step S2 includes: when the lithium cobalt oxide powder sample to be tested is derived from lithium cobalt oxide powder, the pressure factor is the pressure of pressurizing the lithium cobalt oxide powder; or, when the lithium cobalt oxide powder sample to be tested is derived from a lithium cobalt oxide positive electrode sheet, the pressure factor is the compaction density of the electrode sheet.
[0013] Preferably, in step S2, when the number n of lithium cobalt oxide powder samples to be tested and the number N of test channels satisfy n≤N; step S2 comprises: obtaining the specific surface area of the lithium cobalt oxide powder sample to be tested by a multi-round multi-channel method The multi-round multi-channel method includes: subjecting the lithium cobalt oxide powder sample to be tested to multiple rounds of gas adsorption and desorption tests, and in each round of testing, the lithium cobalt oxide powder sample to be tested enters a different test channel, and after multiple rounds of testing, an average value of the test specific surface area is obtained, which is recorded as the specific surface area Since the specific surface area of lithium cobalt oxide powder is small, it is close to the measurement accuracy limit of the specific surface area and porosity analyzer, so direct testing will have a large systematic error. For the case where the number of lithium cobalt oxide powder samples to be tested is less than or equal to the number of test channels of the specific surface area and porosity analyzer, the present application adopts a multi-round multi-channel method for measurement, and each lithium cobalt oxide powder sample to be tested is tested in different test channels, and then the average of the test specific surface areas obtained in multiple rounds of testing is obtained, and the average is used as the specific surface area of the lithium cobalt oxide powder sample to be tested for compressive strength judgment. The multi-round multi-channel method of the present application can effectively eliminate the systematic error when testing in different test channels, which is conducive to improving the accuracy of the specific surface area test, thereby accurately characterizing the compressive strength of the lithium cobalt oxide material.
[0014] In some embodiments, the mass of the lithium cobalt oxide powder sample to be tested in each test channel in each round of testing is 5 to 10 g. The lithium cobalt oxide powder sample to be tested within this mass range can well reflect the overall situation of the lithium cobalt oxide material, and the sample is representative and can more comprehensively characterize the compressive strength of the lithium cobalt oxide material.
[0015] Exemplarily, when the number of lithium cobalt oxide powder samples to be tested is n=3, respectively recorded as sample 1, sample 2 and sample 3, and the number of test channels is N=3, respectively recorded as channel 1, channel 2 and channel 3, the test sequence of multiple rounds and multiple channels can be as shown in Table 1 below.
[0016] Table 1
[0017]
[0018] The specific surface area of the lithium cobalt oxide powder sample to be tested is measured in a multi-round multi-channel manner as shown in Table 1, and the average specific surface area is obtained according to the specific surface area of each round of test, and the average specific surface area is recorded as the specific surface area. For example, the specific surface area of sample 1 in the first round is S 11 The test specific surface area of sample 1 in the second round is S 12 The test specific surface area of sample 1 in the third round is S 13 , the specific surface area of sample 1
[0019] When the lithium cobalt oxide powder samples to be tested are different lithium cobalt oxide materials, the compressive capacity of the lithium cobalt oxide materials can be preliminarily compared based on the specific surface area under the same pressure factor; when the lithium cobalt oxide powder samples to be tested are the same lithium cobalt oxide material, the compressive capacity of the lithium cobalt oxide material can be evaluated based on the specific surface area corresponding to different pressure factors.
[0020] Preferably, in step S2, when the number n of lithium cobalt oxide powder samples to be tested and the number N of test channels satisfy 1<n / N≤5, or when the test interval time d of the lithium cobalt oxide powder samples to be tested is ≤48h; step S2 comprises: obtaining the specific surface area of the lithium cobalt oxide powder samples to be tested by group cross calibration The group cross calibration method includes: dividing the lithium cobalt oxide powder sample to be tested into a calibration group and a non-calibration group; the calibration group contains a calibration sample, wherein the specific surface area of the calibration sample is The non-calibration group contains a calibration sample in the calibration group and a plurality of non-calibration samples to form a cross sample form; the non-calibration samples in the non-calibration group are cross-calibrated with the calibration sample in the calibration group as a reference to obtain the specific surface area of the non-calibration sample. Due to the limited number of test channels of the specific surface area and porosity analyzer, when faced with a large number of lithium cobalt oxide powder samples to be tested, it is necessary to measure in batches. When the specific surface area test values of different samples differ slightly, in order to reduce the standard error of tests between different batches, this application adopts group determination, and one of the groups is used as a calibration group, and one or more lithium cobalt oxide powder samples to be tested are selected from the calibration group as calibration samples. Due to errors, the specific surface areas of the calibration samples measured by different groups are different. This application converts the specific surface areas of the calibration samples in the non-calibration group to be equal to the calibration sample values of the calibration group. Then the samples to be tested in the non-calibration group are converted according to the conversion coefficient of the specific surface area of the calibration samples in the same group, so that the specific surface area results between different test groups can be compared, thereby using the specific surface area to accurately characterize the degree of crushing of the lithium cobalt oxide powder samples to be tested.
[0021] Preferably, the non-calibrated samples in the non-calibrated group are calibrated with the calibration samples in the calibration group as a reference to obtain the specific surface area of the non-calibrated samples. Includes: Get the specific surface area of the calibration sample in the calibration group Get the test specific surface area of the same calibration sample in the non-calibration group Obtain the test specific surface area of the non-calibrated sample in the non-calibrated group Based on formula I, the cross-calibration test specific surface area of the non-calibrated sample in the non-calibrated group is obtained, which is recorded as the specific surface area of the non-calibrated sample Formula I:
[0022] For example, when the number of lithium cobalt oxide powder samples to be tested is n=5, they are recorded as samples 1 to 5, and the number of test channels is N=3, which are recorded as channel 1, channel 2 and channel 3. In the group cross calibration method, samples 1 to 5 are grouped, the first group is used as the calibration group, sample 1 is used as the calibration sample, and the second group is used as the non-calibration group. The test order of the group cross calibration method can be shown in Table 2 below.
[0023] Table 2
[0024]
[0025] The specific surface area of the lithium cobalt oxide powder sample to be tested is measured according to the group cross calibration method in Table 2. The specific surface area of sample 1 as the calibration sample is obtained by a multi-round multi-channel method. For example, in the first group, the test specific surface area of sample 1 in the first round is S 11 The test specific surface area of sample 1 in the second round is S 12 The test specific surface area of sample 1 in the third round is S 13 , the specific surface area of sample 1
[0026] Taking sample 4 of the non-calibrated group as an example, in the second group where sample 4 is located, the test specific surface area of sample 1 in the first round is S 11 ', the test specific surface area of sample 1 in the second round is S 12 ', the test specific surface area of sample 1 in the third round is S 13 ', the test specific surface area of sample 1 The test specific surface area of sample 4 in the first round is S 41 The test specific surface area of sample 4 in the second round is S 42 The test specific surface area of sample 4 in the third round is S 43 , the test specific surface area of sample 4 Based on Formula I, the cross-standard test specific surface area of sample 4 is obtained, that is, the specific surface area
[0027] Preferably, in step S2, when the number n of lithium cobalt oxide powder samples to be tested and the number N of test channels satisfy 5<n / N, or when the test interval d of the lithium cobalt oxide powder samples to be tested is>48h; step S2 comprises: obtaining the specific surface area of the lithium cobalt oxide powder sample to be tested by calibrating the standard sample The calibration standard method includes: the standard sample occupies one test channel, the lithium cobalt oxide powder sample to be tested occupies the other test channels, the standard sample and the lithium cobalt oxide powder sample to be tested enter different test channels in different rounds of testing, and after multiple rounds of testing, the average value of the test specific surface area is obtained, which is recorded as the standard sample test specific surface area. And sample test specific surface area based on and Obtain the specific surface area of the lithium cobalt oxide powder sample to be tested Wherein, the standard sample is a lithium cobalt oxide powder with a known actual specific surface area. For the case where the number n of lithium cobalt oxide samples to be tested and the number N of test channels satisfy 5<n / N, due to the large number of samples, it is impossible to quickly complete the test in a short time, or when the test interval time d of the lithium cobalt oxide powder samples to be tested is >48h, due to the long test interval time, the specific surface area and the detection state of the porosity analyzer are different, which will lead to a large system error. The present application uses a calibration standard sample to calibrate the specific surface area test results of the lithium cobalt oxide powder samples to be tested, which can reduce the system error to a certain extent and improve the accuracy of the specific surface area test.
[0028] Preferably, based on and Obtain the specific surface area of the lithium cobalt oxide powder sample to be tested Including: Based on formula II Formula II: Wherein, S0 is the actual specific surface area of the calibration standard.
[0029] Exemplarily, in step S2, when the number n of lithium cobalt oxide powder samples to be tested and the number N of test channels satisfy 5<n / N, or, when the test interval d of the lithium cobalt oxide powder samples to be tested is>48h, taking lithium cobalt oxide powder samples 1 to 4 to be tested as an example, the number of test channels N=3, which are respectively recorded as channel 1, channel 2 and channel 3, and the test order of the calibration standard method can be as shown in Table 3 below.
[0030] Table 3
[0031]
[0032] The specific surface area of the lithium cobalt oxide powder sample to be tested is measured according to the calibration standard method in Table 3, and the calibration standard is a lithium cobalt oxide powder with a known actual specific surface area S0. The calibration standard occupies one test channel in each round of each test, and the lithium cobalt oxide powder sample to be tested occupies the remaining test channels. In different rounds of testing, the standard standard and the lithium cobalt oxide powder sample to be tested enter different test channels. After multiple rounds of testing, the average value of the test specific surface area is obtained, which is recorded as the standard test specific surface area. And sample test specific surface area Taking sample 1 and calibration standard as an example, the test specific surface area of sample 1 in the first round is S 11 The test specific surface area of sample 1 in the second round is S 12 The test specific surface area of sample 1 in the third round is S 13 , the sample test specific surface area of sample 1 The test specific surface area of the first round of calibration standards is S 01 The test specific surface area of the second round of calibration standard is S 02 The test specific surface area of the third round of calibration standard is S 03 , Standard sample test specific surface area The specific surface area of sample 1 was obtained based on formula II
[0033] Preferably, the step S3 comprises: using the pressure factor T and the specific surface area Obtain the specific surface area corresponding to different pressure factors T Compared with the change rate r of the specific surface area when no pressure factor is applied, based on the specific surface area The rate of change r of the specific surface area under different pressure factors in this application refers to the growth rate of the specific surface area compared to the specific surface area when no pressure factor is applied. For example, when the lithium cobalt oxide powder sample to be tested is derived from lithium cobalt oxide powder, the pressure factor is the pressure of the pressurized treatment, and the specific surface area when no pressure factor is applied refers to the specific surface area S' of the lithium cobalt oxide powder sample corresponding to the pressure of 0 in the pressurized treatment. The rate of change of specific surface area When the lithium cobalt oxide powder sample to be tested is derived from a lithium cobalt oxide positive electrode sheet, the pressure factor is the compaction density of the lithium cobalt oxide positive electrode sheet, and the specific surface area without the pressure factor is the specific surface area S" of the lithium cobalt oxide powder sample obtained by testing the lithium cobalt oxide positive electrode sheet after coating the positive electrode slurry without cold pressing during preparation, drying and sintering. The specific surface area change rate
[0034] Preferably, based on the specific surface area The rate of change of the pressure resistance of the lithium cobalt oxide material is determined; including: when the lithium cobalt oxide powder sample to be tested is derived from lithium cobalt oxide powder, under the condition of the pressurized pressure P, the specific surface area of the sample The change rate of r≤M determines that the compressive strength of the lithium cobalt oxide material is qualified; the specific surface area of the sample The rate of change r>M, it is determined that the compressive resistance of the lithium cobalt oxide material is unqualified, wherein the value range of M is 100%≤M≤200%, and the value range of P is 6t~8t; or, when the lithium cobalt oxide powder sample to be tested is derived from the lithium cobalt oxide positive electrode sheet, under the condition of compaction density Q, the specific surface area of the sample is The rate of change of r≤N determines that the compressive strength of the lithium cobalt oxide material is qualified; the specific surface area of the sample The rate of change r>N determines that the compressive resistance of the lithium cobalt oxide material is unqualified, wherein the value range of N is 35%≤N≤45%, and the value range of Q is 4.1g / cc~4.3g / cc. The present application can judge and determine whether the degree of crushing of the lithium cobalt oxide material to be tested is qualified through the qualified standard range of the specific surface area growth rate. When a pressure of 6 to 8 tons is applied to the lithium cobalt oxide powder and the specific surface area growth rate exceeds 200%, and when the compression of the lithium cobalt oxide positive electrode sheet is 4.1g / cc~4.3g / cc and the specific surface area growth rate exceeds 45%, the degree of crushing of the lithium cobalt oxide material is large, and its performance generally does not meet the application requirements in lithium-ion batteries. According to the different performance requirements of different application scenarios, different specific surface area growth rates can be selected within a certain range as the qualification standard. For example, a pressure of 6 to 8 tons can be applied to the lithium cobalt oxide powder. When the specific surface area growth rate is greater than any value between 100% and 200%, the compressive resistance of the lithium cobalt oxide material to be tested is determined to be unqualified. Alternatively, the compression density of the lithium cobalt oxide positive electrode sheet can be 4.1 g / cc to 4.3 g / cc. When the specific surface area growth rate is greater than any value between 35% and 45%, the compressive resistance of the lithium cobalt oxide material to be tested is determined to be unqualified.
[0035] Based on the above-mentioned method for determining the compressive capacity of the lithium cobalt oxide material of the present application, the compressive capacity of the lithium cobalt oxide material is determined by obtaining the specific surface area of the lithium cobalt oxide powder sample to be tested under different pressure factors. For lithium cobalt oxide powder, the present application uses pressurization treatment to crush the lithium cobalt oxide powder, takes the pressure of the pressurization treatment as the pressure factor, quantifies the degree of crushing of the lithium cobalt oxide powder sample by the specific surface area, and then determines the compressive capacity of the lithium cobalt oxide material; for lithium cobalt oxide positive electrode pieces, the present application uses the compaction density of the piece as the pressure factor, obtains the lithium cobalt oxide powder sample after sintering treatment and measures its specific surface area, and can also determine the compressive capacity of the lithium cobalt oxide material. In addition, according to the measurement characteristics of the specific surface area and porosity measuring instrument, the present application proposes a multi-round multi-channel method, a group cross-calibration method and a calibration standard method for samples of different numbers and measurement intervals to obtain the specific surface area of the lithium cobalt oxide powder sample to be tested, which is conducive to minimizing the system error in the test process and improving the measurement accuracy. This application uses the relationship between the pressure factor and the specific surface area to accurately reflect the compressive resistance of the target lithium cobalt oxide material, and judging from a macroscopic perspective can avoid the limitations of microscopic observation. The judgment method is intuitive and concise, and provides theoretical support for the performance testing of lithium cobalt oxide powder and the performance testing and evaluation of the cold pressing and cycling processes of lithium cobalt oxide positive electrode sheets. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is an appearance diagram of a pole piece after a wound pole piece is directly sintered in a specific implementation manner;
[0037] Figure 2This is an appearance diagram of the lithium cobalt oxide positive electrode plate before and after sintering in a specific embodiment of the present application, wherein the left side shows the hanging state of the electrode plate before sintering, the middle side shows the hanging state of the electrode plate after sintering, and the right side shows the appearance of the electrode plate after sintering;
[0038] Figure 3 XRD patterns of lithium cobalt oxide powder materials after being processed by the traditional winding sintering method and the sintering treatment method of the present application;
[0039] Figure 4 It is a fitting curve diagram of the compacted density and specific surface area of the lithium cobalt oxide powder sample to be tested in Example 1;
[0040] Figure 5 It is the fitting curve diagram of pressure and specific surface area of Example 2;
[0041] Figure 6 The bar and line graphs are the specific surface area growth rates of two lithium cobalt oxide materials at different compaction densities. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0043] The existing technology generally uses microscopic observation to judge the compressive capacity of lithium cobalt oxide materials, which has great limitations and cannot accurately and comprehensively characterize the compressive capacity of lithium cobalt oxide materials.
[0044] In view of this, the present application provides a method for determining the compressive resistance of a lithium cobalt oxide material, comprising at least the following steps: step S1, obtaining a lithium cobalt oxide powder sample to be tested; step S2, obtaining the pressure factor T of the lithium cobalt oxide powder sample to be tested in step S1 and the specific surface area corresponding to the lithium cobalt oxide powder sample to be tested; Step S3: based on the pressure factor T and specific surface area The compressive capacity of the lithium cobalt oxide material is determined.
[0045] In some of the embodiments, in step S1, the lithium cobalt oxide positive electrode sheet to be tested is sintered to remove the binder and the conductive agent to obtain the lithium cobalt oxide powder sample to be tested.
[0046] Traditional sintering is to put the wound electrode directly into a bowl-shaped crucible for sintering. Due to the large amount of electrode samples in this winding and sintering method, the wound electrode pieces will inevitably contact each other, and the heat dissipation at the contact position is poor, which can easily lead to the problem of excessively high local temperature of the electrode piece. Figure 1The figure shows the appearance of a pole piece after the wound pole piece is directly sintered. It can be seen that the color of the contact position of the pole piece after sintering is obviously different from the surrounding area, and there are traces of aluminum foil melting (such as Figure 1 as indicated by the arrow).
[0047] In order to reduce the problem of local over-temperature, in some embodiments, the present application proposes to shear and suspend the lithium cobalt oxide positive electrode sheets, and to perform sintering treatment under the condition that there are gaps between different lithium cobalt oxide positive electrode sheets. Figure 2 The following are the appearance diagrams of the lithium cobalt oxide positive electrode sheet before and after the sintering treatment conditions of the present application. The left side shows the hanging state of the electrode sheet before sintering treatment, the middle side shows the hanging state of the electrode sheet after sintering treatment, and the right side shows the appearance of the electrode sheet after sintering treatment. Figure 2 In this application, the lithium cobalt oxide positive electrode sheet is first unfolded and cut into a suitable size so that it can be placed in the insulation furnace for sintering. Then a hole is punched in the middle of one side of each electrode sheet and it is hung on the sintering bracket, leaving a gap between different lithium cobalt oxide positive electrode sheets to prevent local overheating before subsequent sintering. After the sintering process of this application, the lithium cobalt oxide positive electrode sheet is slightly deformed, but the sintered appearance meets the requirements. Figure 2 As shown in the right figure, the overall color of the pole piece after sintering is uniform, and there is no local color deepening and aluminum foil melting. In addition, the sintering process of this application can process more pole pieces at one time, and nearly 30g of lithium cobalt oxide powder samples to be tested can be collected, which can be used for three specific surface area tests, which is conducive to improving the test efficiency of compressive capacity and saving costs.
[0048] In some of the embodiments, a lithium cobalt oxide positive electrode sheet with a compaction density of 3.9 g / cc was subjected to a conventional winding and sintering method and a sintering treatment method of the present application, respectively. The positive electrode material powder at the melting point of the aluminum foil in the conventional winding and sintering method and the lithium cobalt oxide powder sample to be tested obtained after the sintering treatment method of the present application were subjected to XRD characterization analysis. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the cathode material powder at the melting point of the aluminum foil after the traditional sintering method contains LiAlO2 and Al. These two impurities will undoubtedly make the BET test value larger. The BET specific surface area of the cathode material powder obtained by the traditional method and the lithium cobalt oxide powder sample to be tested obtained by the method of this application was tested. The results showed that the BET test value of the cathode material powder obtained by the traditional method was 0.2655m 2 / g, the BET test value of the lithium cobalt oxide powder sample to be tested obtained by the present application method is 0.215m 2 / g. It can be seen that the present application can avoid or reduce the problem of excessive test specific surface area caused by excessive local temperature by sintering under the condition of gaps between different pole pieces through shearing and hanging treatment, and improve the accuracy and reliability of specific surface area detection of the lithium cobalt oxide powder sample to be tested.
[0049] Optionally, the powder on the lithium cobalt oxide positive electrode plate after sintering can be gently brushed off with a soft brush, so that the powder falls off in the form of small particles to obtain a lithium cobalt oxide powder sample to be tested.
[0050] In some embodiments, the specific surface area test value corresponding to the lithium cobalt oxide powder sample to be tested is obtained by gas adsorption and desorption analysis. Exemplarily, the gas adsorption and desorption analysis includes: vacuum degassing at a temperature of 150 to 200° C. for 1 to 5 hours, then testing the nitrogen adsorption isotherm at a pressure of 0.05 to 0.3 MPa, and calculating the test specific surface area of the lithium cobalt oxide powder sample to be tested.
[0051] In some embodiments, step S3 further includes: using the pressure factor T and the specific surface area Establish a fitting curve to obtain the specific surface area corresponding to different pressure factors T Compared with the change rate r of the specific surface area when no pressure factor is applied, based on the specific surface area The rate of change r of is used to determine the compressive strength of the lithium cobalt oxide material.
[0052] Exemplarily, the fitting curve is a binomial curve, when the specific surface area When the pressure factor T increases in a binomial relationship, the specific surface area can be used to evaluate the crushing of the lithium cobalt oxide material and determine the compressive resistance.
[0053] Example
[0054] The technical solution of the present application is explained below in conjunction with specific embodiments. The raw materials used in the following embodiments are all from common commercially available products, and the devices or equipment used are all purchased from conventional market sales channels. Among them, the battery powder compaction density meter was purchased from Sansi Zongheng, model UTM7305; the specific surface area and porosity analyzer was purchased from Micro Instruments, model TriStarⅡ3020.
[0055] Example 1
[0056] The method for determining the compressive strength of the lithium cobalt oxide material of this embodiment comprises at least the following steps:
[0057] Step S1, take seven lithium cobalt oxide positive electrode sheets, the compaction densities are 3.9g / cc, 4.05g / cc, 4.15g / cc, 4.2g / cc, 4.25g / cc, 4.3g / cc, 4.32g / cc respectively. After unfolding the lithium cobalt oxide positive electrode sheets, shear and hang them, and sinter them under the condition that there are gaps between different lithium cobalt oxide positive electrode sheets. The sintering conditions include: sintering temperature of 600°C and sintering time of 4h. After sintering to remove the binder and conductive agent, use a soft brush to gently brush off the powder on the sheet so that the powder falls off in the form of small particles, and obtain the lithium cobalt oxide powder samples to be tested, which are recorded as samples 1 to 7 respectively.
[0058] Step S2, use a specific surface area and porosity tester to test the nitrogen adsorption isotherm of the lithium cobalt oxide powder sample to be tested, and the test conditions include: 200°C vacuum degassing for 2h, taking 6 points in the pressure range of 0.05-0.3MPa, and calculating the specific surface area test value corresponding to the lithium cobalt oxide powder sample to be tested. The number of test channels N=3, respectively recorded as channel 1, channel 2 and channel 3. Samples 1-7 are tested by group cross-calibration. Samples 1-7 are grouped, the first group is used as the calibration group, sample 1 (4.2g / cc) and sample 3 (4.3g / cc) are used as calibration samples, and the second and third groups are used as non-calibration groups. The test sequence of the group cross-calibration method is shown in Table 4 below.
[0059] Table 4
[0060]
[0061] The specific surface area of the lithium cobalt oxide powder samples to be tested was tested according to the group cross-calibration method in Table 4, and the test specific surface area of each lithium cobalt oxide powder sample to be tested was obtained as shown in Table 5 below.
[0062] Table 5
[0063]
[0064]
[0065] Determine the specific surface area of the lithium cobalt oxide powder sample to be tested according to the test specific surface area in Table 5 The specific surface areas of sample 1 and sample 3, which are calibration samples, are obtained by a multi-round multi-channel method. Based on the specific surface areas of sample 1 and sample 3, the cross-standard test specific surface areas of other samples, i.e., the specific surface areas, are calculated, as shown in Table 6 below.
[0066] Table 6
[0067]
[0068] Step S3: based on the pressure factor T and specific surface area Establish the compaction density ρ and specific surface area of the lithium cobalt oxide powder sample to be tested The fitting curve of Figure 4 As shown, the curve equation is according to Figure 4 It can be seen from the fitting curve that the specific surface area of the lithium cobalt oxide material increases with the increase of the compaction density of the electrode. The fitting curve conforms to the binomial model and can be used to evaluate the compressive resistance of the lithium cobalt oxide material.
[0069] According to the specific surface area results in Table 6, the change rate r of the specific surface area corresponding to different pressure factors T compared to the specific surface area when no pressure factor is applied is obtained. Among them, the specific surface area when no pressure factor is applied refers to the specific surface area S "=0.183g / cc of the lithium cobalt oxide powder sample obtained by testing after the lithium cobalt oxide positive electrode sheet is coated with the positive electrode slurry during preparation without cold pressing, drying and sintering. When the compaction density is 4.15g / cc, the specific surface area change rate r=(0.226-0.183) / 0.183=23.5% is calculated, when the compaction density is 4.2g / cc, the specific surface area change rate r=28.4% is calculated, and when the compaction density is 4.3g / cc, the specific surface area change rate r=31.7% is calculated. Taking the specific surface area change rate of 35% as the qualified standard, under the condition of compaction density of 4.15g / cc~4.3g / cc, the specific surface area change rate r of the lithium cobalt oxide powder sample to be tested is less than 35%, and it is determined that the compressive resistance of the lithium cobalt oxide material is qualified.
[0070] Example 2
[0071] The method for determining the compressive strength of the lithium cobalt oxide material of this embodiment comprises at least the following steps:
[0072] Step S1, pressurizing the lithium cobalt oxide powder, wherein the pressurizing conditions include: a pressure of 0 to 8 tons, a pressure holding time of 5 minutes, and obtaining the lithium cobalt oxide powder sample to be tested;
[0073] Step S2, use a specific surface area and porosity tester to test the nitrogen adsorption isotherm of the lithium cobalt oxide powder sample to be tested, and the test conditions are the same as those in Example 1. The number of test channels N=3, respectively recorded as channel 1, channel 2 and channel 3. Take 6 points from the pressure factor T of 0 to 8t for testing, recorded as samples 1 to 6, corresponding to the test conditions of pressures of 0t, 1t, 2t, 3t, 4t, and 8t, respectively. Due to the large difference in pressure, the specific surface area of the lithium cobalt oxide powder sample to be tested under different pressures also varies greatly. Therefore, there is no need for group cross-calibration, and a multi-round multi-channel method is used for testing. The test method is shown in Table 7 below.
[0074] Table 7
[0075]
[0076] The specific surface area of the lithium cobalt oxide powder samples to be tested was tested in a multi-round multi-channel manner in Table 7, and the test specific surface area of each lithium cobalt oxide powder sample to be tested was obtained as shown in Table 8 below. The average value of the test specific surface area was used as the specific surface area of each lithium cobalt oxide powder sample to be tested.
[0077] Table 8
[0078]
[0079] Step S3: based on the pressure factor T and specific surface area Establishing pressure f and specific surface area The fitting curve of Figure 5 As shown, the curve equation is according to Figure 5 It can be seen from the fitting curve that the specific surface area of the lithium cobalt oxide material increases with the increase of pressure, and the fitting curve conforms to the binomial model, which can be used to evaluate the compressive resistance of the lithium cobalt oxide material.
[0080] According to the specific surface area results in Table 8, the change rate r of the specific surface area corresponding to different pressure factors T compared to the specific surface area when no pressure factor is applied is obtained. Among them, the specific surface area when no pressure factor is applied refers to the specific surface area S'=0.192 of the lithium cobalt oxide powder sample corresponding to the pressure of 0 in the pressurized treatment. When the pressure is 8t, the specific surface area change rate Taking the specific surface area change rate of 100% as the qualification standard, under the condition that the pressure of the pressurized treatment is lower than 8t, the specific surface area change rate r of the lithium cobalt oxide powder sample to be tested is lower than 100%, which determines that the compressive resistance of the lithium cobalt oxide material is qualified.
[0081] Example 3
[0082] The method for determining the compressive strength of the lithium cobalt oxide material of this embodiment comprises at least the following steps:
[0083] Step S1, take 3 lithium cobalt oxide positive electrode sheets, the compaction density is 4.1g / cc, 4.2g / cc, and 4.28g / cc respectively, and record them as samples 1 to 4 respectively with the lithium cobalt oxide positive electrode sheets when no pressure factor is applied. After the lithium cobalt oxide positive electrode sheets are unfolded, they are sheared and suspended, and sintered under the condition that there are gaps between different lithium cobalt oxide positive electrode sheets. The conditions of the sintering treatment include: sintering temperature of 800°C and sintering time of 2h. After the sintering treatment removes the binder and the conductive agent, use a soft brush to gently brush off the powder on the electrode sheet so that the powder falls off in the form of small particles to obtain the lithium cobalt oxide powder sample to be tested.
[0084] Step S2, use a specific surface area and porosity tester to test the nitrogen adsorption isotherm of the lithium cobalt oxide powder sample to be tested, the test conditions are the same as those in Example 1, and the specific surface area test value corresponding to the lithium cobalt oxide powder sample to be tested is calculated. The number of test channels N = 3, respectively recorded as channel 1, channel 2 and channel 3. The test interval time d of the lithium cobalt oxide powder sample to be tested is greater than 48h, so the lithium cobalt oxide powder sample to be tested is tested by a calibration standard sample method, and the standard sample is a known actual specific surface area S0 = 0.186m 2 / g lithium cobalt oxide powder, the test sequence of the calibration standard method is shown in Table 9 below.
[0085] Table 9
[0086]
[0087] The specific surface area of the lithium cobalt oxide powder samples to be tested was tested according to the calibration standard method in Table 9, and the test specific surface area of each lithium cobalt oxide powder sample to be tested was obtained as shown in Table 10. (i.e. the average of the sample test specific surface area) and the calibration standard test specific surface area (i.e. the average specific surface area of the calibration standard sample), combined with the actual specific surface area S0 of the standard sample, the specific surface area of samples 1 to 4 is calculated
[0088] Table 10
[0089]
[0090] Step S3: based on the pressure factor T and specific surface area The change rate r of the specific surface area corresponding to different pressure factors T compared with the specific surface area of sample 1 is obtained. When the compaction density is 4.1g / cc, the specific surface area change rate r=(0.241-0.186) / 0.186=29.6% is calculated, when the compaction density is 4.2g / cc, the specific surface area change rate r=(0.246-0.186) / 0.186=32.3% is calculated, and when the compaction density is 4.28g / cc, the specific surface area change rate r=(0.268-0.186) / 0.186=44.1% is calculated. Taking the specific surface area change rate of 35% as the qualified standard, under the condition of compaction density of 4.1g / cc to 4.3g / cc, the change rate r of the specific surface area of the lithium cobalt oxide powder sample to be tested determines that the compressive resistance of the lithium cobalt oxide material is unqualified.
[0091] Test example
[0092] The method of Example 1 was used to test the compressive strength of the two lithium cobalt oxide positive electrode sheets, and the compaction density and specific surface area results obtained are shown in Table 11 below.
[0093] Table 11
[0094]
[0095] According to the data in Table 11, the bar graph and line graph of the specific surface area growth rate of the two lithium cobalt oxide materials at different compaction densities are drawn as follows: Figure 6 As shown in Table 11 and Figure 6 As shown, when the compaction density is 4.1g / cc, 4.2g / cc and 4.28g / cc respectively, the specific surface area growth rate corresponding to the lithium cobalt oxide material 1 is 26.6%, 31.3% and 35.4% respectively, and the specific surface area growth rate corresponding to the lithium cobalt oxide material 2 is 48.4%, 52.2% and 52.8% respectively. The method of Example 2 is used to detect the compressive strength of the two powdered lithium cobalt oxide materials. The two lithium cobalt oxide powder samples are cold pressed with 8t pressure. Compared with the lithium cobalt oxide powder in the corresponding initial state, the specific surface area growth rate of the lithium cobalt oxide powder 1 is 115%, and the specific surface area growth rate of the lithium cobalt oxide powder 2 is 250%. The specific surface area growth rate results measured by the two methods both show that the lithium cobalt oxide material 1 exhibits better compressive strength at both the powder and pole piece levels. It can be seen that whether it is powder or pole piece, the method of the present application can accurately and intuitively judge whether the compressive strength of the lithium cobalt oxide material to be tested is qualified by the specific surface area of the lithium cobalt oxide material under different pressure factors. This scheme can form a standardized judgment method, which is conducive to promotion and application. It is of great significance for the performance measurement of lithium-ion batteries and the research on the compressive resistance of lithium cobalt oxide materials.
[0096] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for determining the compressive strength of a lithium cobalt oxide material, characterized in that: At least the following steps are included: Step S1, obtaining a lithium cobalt oxide powder sample to be tested; Step S2: Obtain the pressure factor T of the lithium cobalt oxide powder sample to be tested in step S1 and the specific surface area corresponding to the lithium cobalt oxide powder sample to be tested Step S3: based on the pressure factor T and specific surface area The compressive capacity of the lithium cobalt oxide material is determined.
2. The determination method according to claim 1, characterized in that: Step S1 comprises: pressurizing the lithium cobalt oxide powder to obtain the lithium cobalt oxide powder sample to be tested; or, The lithium cobalt oxide positive electrode sheet to be tested is sintered to remove the binder and the conductive agent, so as to obtain the lithium cobalt oxide powder sample to be tested.
3. The determination method according to claim 2, characterized in that: The conditions for the pressurization treatment in step S1 include: The pressure is 0-8t, and the holding time is 3-20min; Alternatively, the sintering conditions in step S1 include: The sintering temperature is 600-800°C, and the sintering time is 2-4h.
4. The determination method according to claim 2, characterized in that: The sintering process in step S1 includes: The lithium cobalt oxide positive electrode sheets are sheared and suspended, and sintered under the condition that there are gaps between different lithium cobalt oxide positive electrode sheets.
5. The determination method according to claim 2, characterized in that: The pressure factors in step S2 include: When the lithium cobalt oxide powder sample to be tested is derived from lithium cobalt oxide powder, the pressure factor is the pressure of pressurizing the lithium cobalt oxide powder; or When the lithium cobalt oxide powder sample to be tested is derived from a lithium cobalt oxide positive electrode sheet, the pressure factor is the compaction density of the electrode sheet.
6. The determination method according to claim 1, characterized in that: In step S2, when the number n of lithium cobalt oxide powder samples to be tested and the number N of test channels satisfy n≤N; The step S2 comprises: obtaining the specific surface area of the lithium cobalt oxide powder sample to be tested by a multi-round multi-channel method. The multi-round multi-channel method includes: subjecting the lithium cobalt oxide powder sample to be tested to multiple rounds of gas adsorption and desorption tests, and in each round of testing, the lithium cobalt oxide powder sample to be tested enters a different test channel, and after multiple rounds of testing, an average value of the test specific surface area is obtained, which is recorded as the specific surface area 7. The determination method according to claim 6, characterized in that: In step S2, when the number n of lithium cobalt oxide powder samples to be tested and the number N of test channels satisfy 1<n / N≤5, or when the test interval time d of the lithium cobalt oxide powder samples to be tested is ≤48h; The step S2 comprises: obtaining the specific surface area of the lithium cobalt oxide powder sample to be tested by group cross calibration The group cross calibration method includes: Dividing the lithium cobalt oxide powder samples to be tested into a calibration group and a non-calibration group; The calibration group contains calibration samples, wherein the specific surface area of the calibration samples is Obtained through multiple rounds and multiple channels; The non-calibrated group contains the same calibration sample in the calibration group and multiple non-calibrated samples to form a cross sample format; Based on the calibration samples in the calibration group, the non-calibration samples in the non-calibration group are cross-calibrated to obtain the specific surface area of the non-calibration samples.
8. The determination method according to claim 7, characterized in that: Based on the calibration samples in the calibration group, the non-calibration samples in the non-calibration group are calibrated to obtain the specific surface area of the non-calibration samples. include: Get the test specific surface area of the calibration sample in the calibration group Get the test specific surface area of the same calibration sample in the non-calibration group Obtain the test specific surface area of the non-calibrated sample in the non-calibrated group Based on formula I, the cross-calibration test specific surface area of the non-calibrated sample in the non-calibrated group is obtained, which is recorded as the specific surface area of the non-calibrated sample 9. The determination method according to claim 1, characterized in that: In step S2, when the number n of lithium cobalt oxide powder samples to be tested and the number N of test channels satisfy 5<n / N, or when the test interval time d of the lithium cobalt oxide powder samples to be tested is>48h; The step S2 comprises: obtaining the specific surface area of the lithium cobalt oxide powder sample to be tested by means of a calibration standard. The calibration standard method includes: the standard sample occupies one test channel, the lithium cobalt oxide powder sample to be tested occupies the other test channels, the standard sample and the lithium cobalt oxide powder sample to be tested enter different test channels in different rounds of testing, and after multiple rounds of testing, the average value of the test specific surface area is obtained, which is recorded as the standard sample test specific surface area. And sample test specific surface area based on and Obtain the specific surface area of the lithium cobalt oxide powder sample to be tested Wherein, the standard sample is lithium cobalt oxide powder with known actual specific surface area.
10. The determination method according to claim 9, characterized in that: based on and Obtain the specific surface area of the lithium cobalt oxide powder sample to be tested include: Based on formula II Wherein, S0 is the actual specific surface area of the calibration standard.
11. The determination method according to claim 1, characterized in that: The step S3 comprises: Using the pressure factor T and specific surface area Obtain the specific surface area corresponding to different pressure factors T Compared with the change rate r of the specific surface area when no pressure factor is applied, based on the specific surface area The rate of change r of is used to determine the compressive strength of the lithium cobalt oxide material.
12. The determination method according to claim 11, characterized in that: Based on the specific surface area The rate of change of the lithium cobalt oxide material is used to determine the compressive strength of the lithium cobalt oxide material; comprising: When the lithium cobalt oxide powder sample to be tested is derived from lithium cobalt oxide powder, under the condition of pressurization pressure P, the specific surface area of the sample is The change rate of r≤M determines that the compressive strength of the lithium cobalt oxide material is qualified; the specific surface area of the sample The rate of change r>M, it is determined that the compressive strength of the lithium cobalt oxide material is unqualified, Wherein, the value range of M is 100%≤M≤200%, and the value range of P is 6t~8t; or, When the lithium cobalt oxide powder sample to be tested is derived from a lithium cobalt oxide positive electrode sheet, under the condition that the compaction density is Q, the specific surface area of the sample is The rate of change of r≤N determines that the compressive strength of the lithium cobalt oxide material is qualified; the specific surface area of the sample The rate of change r>N, it is determined that the compressive strength of the lithium cobalt oxide material is unqualified, Among them, the value range of N is 35%≤N≤45%, and the value range of Q is 4.1g / cc~4.3g / cc.
Citation Information
Cited By
Quantization method for cracking degree of lithium ion battery pole piece
CN121632758A
